El poblamiento de Amrica - Suarez Aguirre, Francis Jhosei (2019)
The settlement of America is one of the events of history, which currently continues to present controversies, since to date it has not been possible to verify the exact route, where they populated the American continent. This has generated that different, archaeologists, studious scientists of this branch; Look for the evidence you allow, at once to end these assumptions that have been generated regarding the issue. Thus, there are a variety of theories concerning the American population; however only four are the most prominent; On the other hand, this topic turns out to be more interesting for all the American inhabitants of the continent, since if it is possible to find the route of origin to America, it identifies us a little more with our ancestors